Exploration of the Foreign Exchange Forward Premiums and the Spot Exchange Return: A Multivariate Approach - Hamzaoui, Nessrine; Regaieg, Boutheina (International Journal of Economics and Financial Issues, 2016)
This paper empirically examines the interdependence between the foreign exchange forward premiums and the spot exchange return through a Multivariate GARCH type framework. The purpose of this study is to test the correlation sensitivity to shocks and the to capture the dynamic links between the EUR/USD 1,3, 6, 9 and 12-month forward premiums and the spot exchange return. Our empirical analysis is based on daily data from January 8, 1999 to January 8, 2016. Our daily analysis reveals the presence of high correlations between the unconditional EUR/USD forward exchange premiums at different horizons and the possible effect of asymmetric shocks on the conditional variance. The estimation results show that the dynamic conditional correlations have a relatively small and insignificant autoregressive effect, in addition to the existence of significant correlation sensitivity to shocks. Keywords: Forward premium anomaly, DCC-MVGARCH, conditional volatility, Volatility Persistence. JEL Classifications: F31, C22, C58, G15.